Context matters: Oil palm production and women's dietary diversity in the tropical forest of Cameroon - Tabe-Ojong, Martin Paul Jr. (Wiley, 2024)
Oil palm is one of the most rapidly expanding food and cash crops in many tropical regions with significant environmental implications, but also economic gains. Previous analyses have established that this expansion is associated with changing gender roles and time allocation for women. Time allocation is an important determinant of maternal and child nutrition as well as well-being. We use a rich farm household survey from a native oil palm production hotspot, Cameroon, to examine the associations between oil palm production and women's dietary diversity. Using different estimation and identification strategies with some sensitivity checks, we show that oil palm is associated with lower dietary diversity for women, measured as the minimum dietary diversity for women and the minimum adequacy diversity diet. We explore heterogeneity in the various food groups consumed by women and show that oil palm production is associated with lower consumption of mainly pulses, fruits and vegetables. These findings contrast with the literature that has established some positive dietary diversity implications of oil palm expansion in Southeast Asia. We carefully discuss these findings and argue that context matters and may explain these differences. Particularly, we show that oil palm production is negatively associated with farm production diversity in Cameroon. Notwithstanding, we also confirm previous findings that highlight that oil palm production is associated with higher income. These insights add to the debate on the implications of oil palm expansion in tropical environments. Moreover, they can guide policy in designing more tailored interventions that address nutrition issues and improve rural development.